Utilizing Seismic Attributes to Enhance Deduction of the subtle stratigraphic trap in Mishrif Formation at Dujaila oil field, Southern East of Iraq - Khawaja, Ahmed Muslim Attallah; Thabit, Jassim Muhammad (Iraqi Journal of Science, 2022)
Three seismic instantaneous attributes (phase, frequency, and variance) were utilized on 3D-seismic poststack migrated data, covering 617.31 km2, integrated with data of two wells (Du-1 and Du-2) in Dujaila oil field, southeast of Iraq. They gave good results in detecting reef buildups and confirmed the existence of the stratigraphic hydrocarbon trap that was not obvious in the conventional seismic amplitude sections. They display several seismic criteria in attribute sections for recognizing reef buildups and hydrocarbon accumulation, such as phase reversal, low frequency, and high amplitude variance. The seismic attributes emphasized that the stratigraphic trap of reef rudist buildups with hydrocarbon content is constricted in the upper part of the Mishrif Formation (Cenomanian-Early Turonian) the vicinity around productive well Dujaila-1. It is located at a time from -1730 ms in the Top Mishrif to underneath at a time -1775 ms, which has correspondent the depth 2825 m to 2887.5 m, respectively. This stratigraphic trap covered 70 km2 (length is 10.0 km in direction N-S, and the width is about 7.0 km in the E-W direction). The enclosure of the stratigraphic trap extends about 7 km towards SW from the well Dujaila-1 and did not reach well Dujaila-2 (Du-2). That may explain why it was dry. As a result, the circular region around well Du-1 of a radius of about 4 km, and the area extended about 7 km toward SW from well Du-1 represent a zone of low risk-drill for new exploration wells.